Impact of Acceptance and Commitment Therapy (ACT) on Medication Adherence of People with Schizophrenia - Apri Rahma Dewi; Achir Yani S Hamid; Herni Susanti (KHD-Production, 2023)
Ineffective health management and adherence are the problems of mentally ill patients. Thus, if left untreated, they could create significant disadvantages for clients, their families, the community, and even the government. This case study aimed to identify the effect of Acceptance and Commitment Therapy (ACT) on clients with Ineffective health management and to identify adherence, acceptance, and commitment to the regimen. The research approach used in this study was case study conducted on 5 respondents consisting of mentally ill patients with Ineffective health management. The ACT was given for 4 sessions through two to four meetings. The analyzed clients were measured using MARS (Medication Adherence Rating Scale). After the client was given ACT and nursing intervention, the adherence increased by 71% (14 points), and the acceptance ability and commitment increased to 70% on five clients. Medication adherence, acceptance, and commitment levels were lower in the younger clients, who get stigma and lack of family support. Mentally ill patients given ACT will survive more than others without ACT because they have agreed to stay healthy by taking medication regularly. So, this study recommended ACT to increase the health management of mentally ill patients as the approach to increase adherence and commitment to treatment.